Efficacy of drugs treatment in patients with endometrial hyperplasia with or without atypia: A systematic review and network meta-analysis - Yao, Yingsha; Xu, Shuhang; Wang, Ting; Jiang, Ruoan (Medicine (Baltimore), 2024)
Background: Endometrial hyperplasia (EH) is a hyperplastic endometrial lesion with irregular gland size, increased glands, and increased glandular interstitial ratio. During follow-up, some EH progressed further to endometrial cancer. It is crucial to provide timely treatment for EH and improve the overall prognosis of EH patients. Methods: We searched the PubMed, ClinicalTrials.gov., and Embase databases for studies published from their inception to March 31, 2023. The methodological quality of each study was evaluated in accordance with the Cochrane Collaboration's tool for assessing the risk of bias. The RevMan5.3 software provided by the Cochrane Collaboration was used for direct meta-analysis statistical analysis; and the relative risk and 95% confidence interval along with the mean difference and 95% confidence interval, were used as evaluation indexes. Results: We included 21 randomized controlled trials involving a total of 2276 women with EH, 6 studies were of high quality, and 15 were of moderate quality. The blinding of subjects and intervention providers was identified as the main source of potential bias. Six interventions were addressed in the network meta-analysis: medroxyprogesterone acetate (MPA), plus metformin, norethisterone (NET), levonorgestrel-releasing intrauterine system (LNG-IUD), megestrol acetate, and other drugs. In the direct meta-analysis, we found the probability of endometrial complete regression (CR) in the LNG-IUD group to be significantly higher than those in the NET. In the network meta-analysis, we found the probability of CR in the NET group to be significantly lower than those in the MPA and plus metformin groups, the probability of CR in the LNG-IUD group to be significantly higher than those in the NET, the probability of CR in the other drugs group to be significantly higher than those in the LNG-IUD. The NET group had the lowest incidences of endometrial complete regression, plus metformin could have a better outcome. Conclusion: According to the 21 randomized controlled trials included in this study, MPA is the most effective for EH endometrial outcome when applied as a single agent, while the combination of metformin can achieve a more significant effect.